Physicochemical characteristics of Pajuro seeds (Erythrina edulis Triana) and functional properties after the extrusion - Delgado-Soriano, Víctor (2020)
The aim of the present study was to determine the physico-chemical characteristics of pajuro seeds (Erythrina edulis Triana) and the effects of temperature and moisture on the functional properties of extruded seeds. The mature seeds were conditioned for their physical-chemical characterization and extrusion under three temperature conditions (110, 120 and 130 °C) and two moisture levels (13 and 18%). The results of the physico-chemical characteristics were presented in terms of averages and standard deviations, while the data of the functional properties were submitted to ANOVA under a Completely Randomized Design with 3x2 factorial arrangement and for the comparison of means the Tukey's (p˂0.05) test was used. The seeds presented values of color in the hull like L* (27.26), a* (8.60) and b* (4.81), dimensions of length (4.35 cm), width (2.58 cm) and thickness (1.28 cm); likewise, a value of 478.96 g was recorded for the weight of 100 seeds, percentages of hull (10.8%) and cotyledons (89.2%) with respect to the whole seed, and water activity (0.983) at 66% moisture. Pajuro seeds extruded at 130 ºC and 13% of moisture showed better functional properties, for the expansion index (2.58 cm), water absorption index (7.57%) and water solubility index (38.85%). The characteristics of the whole seeds as extruded, place the pajuro as a potential food for the development of new products that will satisfy the needs of the consumer.